Sistem Keamanan Pintu Rumah dengan Pengenalan Wajah Menggunakan ESP 32 Cam: "Sistem Keamanan Pintu Rumah dengan Pengenalan Wajah Berbasis ESP 32 Cam: Solusi Cerdas untuk Keamanan Rumah Anda" - Adi Winarno; Dimas Ricky Saputra; Adi, Winarno (BEST, 2024)
The development of science and technology, especially in the fields of Electronics and Informatics, is expected to enhance room or home security systems, particularly home door security systems. Many door security technologies have been developed to prevent and ensure the comfort of homeowners when they leave their homes. Some commonly used door security systems include CCTV cameras, fingerprint sensors, voice sensors, and RFID. However, with technological advancements, these security systems have shown vulnerabilities, such as frequent errors in fingerprint and voice sensors. Based on this, to create a more secure and innovative home door security system, the authors developed a security system with face detection and a remote warning notification system using Telegram. The researchers created a door security system using the ESP 32-CAM for face detection and as a controller for the Internet of Things (IoT) system. Additionally, a manual system using a keypad for password input was also created. The results of this study include the accuracy and speed of face recognition and the speed of sending security system warning information through the Telegram application.